The Baroque: the intellectual and geopolitical reasons for a historiographical erasure - Jesús Pérez-Magallón (Les Dossiers du GRIHL)
“The Baroque: the intellectual and geopolitical reasons for a historiographical erasure” highlights the need for a new way of conceptualizing the Baroque, taking into account the period’s plurality of discourses and diverging tendencies, specifically in respect to the modernity project conceived by the dominant European nations of the Enlightenment. As opposed to Antonio Maravall’s univocal paradigm of a guided culture of the masses, the Baroque was a much more multivocal period of time containing various emerging and subaltern discourses which greatly contributed to the rationalist and scientific thought of the Enlightenment. Despite this fact, the Baroque and the Enlightenment came to be seen as antithetical. Consequently, the Baroque and the Iberian Peninsula were erased from the grand narrative of European and Western modernity. Emphasizing its uncivilized character, Northern European nations metaphorically displaced the Spanish Empire to the periphery of modern Europe. Using propagandistic means to cast the Iberians to the margins, the nations belonging to the modernity project painted themselves as the “natural” heirs of the Enlightenment, consolidating their political hegemony. The process of writing the grand narrative of modernity involved appropriating several key criteria from the Baroque and consequently erasing their original place of belonging. Keeping this manipulation of history in mind permits a double reading of the course leading to modernity. My paper calls for a new way of interpreting this period of time which emerged at the end of the sixteenth century and continued until the Cádiz Cortes and the independence of the American colonies. This alternate hermeneutic would entail a coming together of the Baroque and the Enlightenment; a dynamic, complex, and conflicting process establishing a modernity which would continue into the modernity of today.